THE USE OF NOTE-TAKING PAIRS IN DEVELOPING STUDENTS’ WRITING SKILL OF RECOUNT TEXT (A True Experimental Study at Eighth Grade Students of MTs. Negeri 1 Jepara in The Academic Year of 2018/2019) - Fiskha Wulandari (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The objective of this study was to find out the significant difference between writing skill of students taught with Note-Taking Pairs and who are not at the eighth grades of MTs. Negeri 1 Jepara in the academic year 2018/2019. This study was true experimental design exactly Pretest-Posttest control group Design that involving two groups of classes. One group treated as the experimental class and other group treated as controlled class. In the experimental class, the writer applied Note-Taking Pairs and in controlled class, the writer applied conventional teaching strategy. The population of this study was the eighth grades students of MTs. Negeri 1 Jepara which consisted of 377 students. The samples of the study consisted of 72 students which were taken by using simple random sampling, VIII E consisted of 36 students as experimental class and VIII F consisred of 36 students as controlled class. There were two variables in this study: Note-Taking Pairs as the independent variable and students’ writing skill as the dependent variable. The instrument of this study was writing recount text test. The result of the research indicated that there was a significant difference between students’ post-test in both experimental and control classes. In experimental class, the total mean score of the post-test was 83.78 and the total mean score in control class was 63.28. It can be seen from that result that the score in experimental class was higher than that of control class. From the t-test, the writer found that the value of the t-test in the post test was greater than the t-table (9.511 > 2.000). Based on the findings and the discussion of the study, the writer draw a conclusion that the use of Note-Taking Pairs is effective to develop students’ writing skill at the eighth grades of MTs. Negeri 1 Jepara.